Tourist perception towards Kelantanese food image / Hanif Hanan and Zuliah Abd Hamid - Hanan, Hanif; Abd Hamid, Zuliah (Faculty of Hotel and Management, Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2017)
Food tourism is not a new phenomenon or trend that promotes the tourism products in Malaysia. The unique combination of multiple ethnicities and cultures influence the taste of the food that is served. Some of the food have been influenced by the other cultures based on the geographical elements where the region is related to other strong cultural regions. For example, Kelantan food have been influenced by Thai food where both destinations are next to each other. However, the slogan of the tourism promotion in Kelantan is the ‘cradle of Malay culture’ where it shows Kelantan itself has a strong image of Malays which includes the food. The slogan tells that Kelantan food image is the real Malay food image that has been preserved from generation to generation but in reality, the geographical and other cultural influences are also the important elements that need to be considered in measuring the food image of the region. Thus, this paper will explain and expand on the food tourism element and the destination and food image that influence visitors visiting the tourism destination of Kelantan.